موانع الشهادة عند المالكية من خلال كتاب تبصرة الحكام لابن فرحون المالكي 799ه دراسة تأصيلية تطبيقية - محمد مقدمي; توفيق بن عبود (University of eloued جامعة الوادي, 2025)
"تتناول هذه الدراسة موضوع موانع الشهادة في المذهب المالكي من خلال تحليل كتاب ""تبصرة الأحكام في أصول القضايا ومناهج الأحكام"" للقاضي الإمام برهان الدين إبراهيم بن فرحون المالكي (ت799هـ)، الذي يُعد من أهم المراجع في الفقه المالكي والقضاء الإسلامي. تهدف الدراسة إلى تعريف الشهادة في المذهب المالكي كما وردت في كتاب تبصرة، مع إبراز شروط قبولها وضوابطها، بالإضافة إلى استقراء موانع الشهادة وتصنيفها وفقاً لمنهج ابن فرحون اعتمد البحث على المنهج الوصفي والاستقرائي، حيث جُمعت النصوص الشرعية المتعلقة بالشهادة وموانعها من القرآن الكريم والسنة النبوية، مع التركيز على نصوص كتاب تبصرة الأحكام، وتحليلها. كما استعرض البحث جهود ابن فرحون العلمية ودوره في ترسيخ القضاء على المذهب المالكي، وبيّن أهمية الشهادة في تحقيق العدالة ومنع الظلم، كونها وسيلة رئيسية لإثبات الحقوق أمام القضاء. قُسِّم البحث إلى مبحثين رئيسيين: الأول خُصص لتعريف الشهادة وأدلتها الشرعية وحكمها وشروطها ومراتبها عند ابن فرحون، أما المبحث الثاني فركز على استقراء موانع الشهادة وتصنيفها إلى موانع تتعلق بالشاهد، وموانع تتعلق بالمشهود عليه، مع تقديم نماذج تطبيقية من كتاب التبصرة, وفي الختام عَرَض البحث أهم النتائج التي توصل إليها، منها أن موانع الشهادة متعددة ومتفرقة في كتب الفقه المالكي، وأن كتاب التبصرة يقدم تصنيفاً منهجياً دقيقاً لها، كما أكد على ضرورة تحقق عدالة الشهود وخلوهم من الموانع لضمان سلامة الإجراءات القضائية. واجه البحث بعض الصعوبات مثل عدم وجود عنوان مستقل لموانع الشهادة في كتاب التبصرة، مما استلزم تتبعاً دقيقاً للنصوص، وكذلك التداخل بين مصطلحي الموانع والشروط عند بعض الفقهاء، إضافة إلى تحديات الربط بين الموانع الفقهية القديمة والمعاصرة. تُعد هذه الدراسة إضافة طبية مُهمة تُسلط الضوء على موضوع حساس في الفقه المالكي، وتُثري الدراسات الفقهية بتحليل معمق لمنهج ابن فرحون، مع إمكانية الاستفادة من نتائجها في تطوير النظم القضائية الإسلامية الحديثة، خاصة في مجال الشهادة وإثبات الحقوق بما يحقق العدالة ويمنع الظلم في المجتمع. This study addresses the topic of impediments to testimony in the Maliki school through an analysis of the book ""Tabsirat al-Ahkam fi Usul al-Qada wa Manahij al-Ahkam"" by the judge and scholar Burhan al-Din Ibrahim ibn Farhun al-Maliki (d. 799 AH), one of the most important references in Maliki jurisprudence and Islamic judiciary. The study aims to define testimony in the Maliki school as presented in Tabsira, highlighting the conditions and rules for its acceptance, as well as surveying and classifying the impediments to testimony according to Ibn Farhun's methodology. The research employs descriptive and inductive methods, collecting relevant Islamic texts on testimony and its impediments from the Qur'an and Sunnah, with a focus on the texts of Tabsirat al-Ahkam for analysis. It also reviews Ibn Farhun's scholarly contributions and his role in consolidating Maliki judiciary, emphasizing the importance of testimony in achieving justice and preventing injustice as a primary means of proving rights before the court. The study is divided into two main sections: the first defines testimony, its legal evidences, ruling, conditions, and ranks according to Ibn Farhun; the second surveys the impediments to testimony, classifying them into those related to the witness and those related to the subject of testimony, with practical examples from Tabsira. The conclusion presents key findings, including the multiplicity and dispersion of impediments in Maliki jurisprudence texts and the precise systematic classification provided by Tabsira. It also stresses the necessity of witnesses’ justice and absence of impediments to ensure proper judicial procedures. The research faced challenges such as the absence of a dedicated chapter on impediments in Tabsira, requiring meticulous tracking of texts, the overlap between the terms ""impediments"" and ""conditions"" among some jurists, and difficulties linking classical and contemporary jurisprudential impediments. This study is a significant scholarly contribution shedding light on a sensitive topic in Maliki jurisprudence, enriching fiqh studies with an in-depth analysis of Ibn Farhun's approach, and offering insights useful for developing modern Islamic judicial systems, especially in testimony and proof of rights to achieve justice and prevent injustice in society.
ماستر شريعة
Keywords: كتاب تبصرة الحكام; المالكية; موانع الشهادة; Impediments to Testimony; Maliki; Book of Insight for Rulers